Diet of juvenile Percichthys trucha (Teleostei: Percichthyidae) in Northern Patagonia: the importance of the littoral zone - Fernández, María Valeria (2020)
The creole perch, Percichthys trucha is endemic to southern South America. The objective of this work was to identify the food groups of juvenile perch (up to one year old) in its natural environment, the Espejo Chico Lake. A total 99 individuals fromwere caught, measured and weighed, and their condition factor (K) was calculated. In the diet analyses, nine different groups (orders) were found in the stomach contents: Diplostraca, Cyclopoida, Amphipoda, Diptera, Coleoptera, Ephemeroptera, Plecoptera, Hymenoptera and Odonata. Food items showed no correlation with fish size (<29, 30-49, 50-69 and 70-89 mm). Diptera and amphipods inhabiting littoral areas were the main food items of the juveniles. We can suppose that the Creole perch prefer the littoral zone as a nursery; this obviates the need to migrate to the limnetic zone, since the littoral zone provides better food, stable physical habitats and refuge, and a higher concentration of dissolved oxygen than deeper zones, both for macroinvertebrates and perch.